Роль маркетингу в підвищенні конкурентоспроможності молококонсервної продукції - Гнатенко, Олена Андріївна (My University, 2012)
Розглянуто роль маркетингу в підвищенні конкурентоспроможності молококонсервної продукції. Визначено місце маркетингу в менеджменті організації. Запропоновано схему видів маркетингу, яка дозволяє залежно від коливань попиту міняти стратегію поведінки підприємства на ринку та застосовувати той або інший вид маркетингу, що дозволить в тій чи іншій мірі впоратися з проблемою зниження конкурентоспроможності продукції та збільшити обсяги продажів.

A marketing role is considered in the increase of competitiveness of sucklings milk products. A marketing place is certain in the management of organization. The chart of kinds is offered to marketing, which allows depending on the vibrations of demand to change strategy of conduct of enterprise at the market and apply the that or other type of marketing which will allow in one or another measure to manage with the problem of decline of competitiveness of products and increase the volumes of sales.
Keywords: маркетинг; кафедра фінансів; marketing; конкурентоспроможність продукції; консервна продукція; competitiveness of products; sucklings products